Government of Jammu and Kashmir Draft Annual Plan 1982-83 Volume IX - Government of Jammu and Kashmir (Government of Jammu and Kashmir, 1982)
The Draft Annual Plan for 1982–83 of Jammu and Kashmir presents a comprehensive development strategy aimed at addressing socio-economic challenges through targeted investments in infrastructure, social welfare, employment generation, and rural development. The plan prioritizes the housing sector by providing loans and assistance to government employees and low- and middle-income groups while expanding housing site allotments to mitigate the acute shortage of residential facilities. Special attention is given to police housing, with substantial allocations intended to improve living conditions for law enforcement personnel and enhance institutional efficiency. Urban development initiatives focus on environmental improvements in cities such as Srinagar and Jammu, including slum upgrading, civic amenities enhancement, and the development of Dal Lake as an environmental and tourism asset. Significant resources are also dedicated to water supply and sanitation projects aimed at expanding access to potable water in both rural and urban areas, improving sewerage systems, and promoting sanitation infrastructure. Public works programs emphasize the construction and rehabilitation of government buildings, truck terminals, and road infrastructure to strengthen administrative and transport capabilities. The plan also addresses rising unemployment through self-employment initiatives, training programs, and support for small enterprises, with particular emphasis on the growing number of educated unemployed youth. Social welfare programs form another key component, with allocations for child welfare, nutritional support, women’s vocational training, scholarships for disadvantaged groups, and services for physically challenged individuals. Special development initiatives for marginalized communities such as the Gujjars and Bakerwals include mobile schools for migratory populations, housing assistance, scholarships, and support for small trade activities to promote economic integration and educational access. Additionally, the Desert Development Agency in Kargil outlines sectoral programs aimed at strengthening agriculture, irrigation, animal husbandry, fisheries, forestry, and cooperative development to improve rural livelihoods in arid regions. Overall, the Annual Plan integrates infrastructure development, social equity measures, employment generation, and environmental management into a coordinated framework designed to improve living standards, reduce regional disparities, and promote sustainable socio-economic development across Jammu and Kashmir.
Planning and Development Department Jammu November, 1981
Planning and Development Department Jammu November, 1981
Keywords: Jammu and Kashmir Annual Plan 1982–83; Housing and Urban Development Programs; Police Housing Infrastructure; Water Supply and Sanitation Development; Public Works and Infrastructure Projects; Employment Generation and Self-Employment Schemes; Social Welfare and Child Development; Women Empowerment and Vocational Training; Development of Gujjars and Bakerwals; Desert Development Agency Kargil; Agricultural and Animal Husbandry Development; Rural Infrastructure and Irrigation Programs